Discontinuity, cultural evolution and the historic event - Van der Waals, J (Proceedings of the Society of Antiquaries of Scotland, 1985)
Continuity and discontinuity are considered as functions of the evolution of culture, with particular reference to Late Neo transformations (Battle Axe Culture and Bell Beaker problems). Historic elements cannot be overlooked.